KREATIFITAS GURU PAI DALAM PENGGUNAAN MEDIA PEMBELAJARAN AUDIO VISUAL DI SMP AL-ISLAM 1 SURAKARTA - Nuranisa Handini; Mukhlis Fatkhurrohman; Herri Gunawan (Institut Islam Mamba'ul 'Ulum Surakarta, 2022)
The purpose of this study was to describe the creativity of PAI teachers in the use of audio-visual learning media at SMP Al-Islam 1 Surakarta. This research is a qualitative research with a qualitative descriptive approach. The subject of this research is SMP Al-Islam 1 Surakarta. The technique used in this research is observation, interview, and documentation. Meanwhile, data analysis uses data reduction, data presentation, and drawing conclusions. The results of this study indicate that with PAI teacher planning in the use of audio-visual learning media, teachers can plan the learning process by utilizing video and powerpoint as a message delivery in learning. Also, the creative efforts of PAI teachers in using audio-visual learning media are quite creative. PAI teachers make good use of the facilities and infrastructure available at the school. The types of media used, namely: LCD, laptop, and sound. By using audio-visual media, teachers can develop new ideas in the learning process and can make it easier for students to understand the material presented by the teacher so that the learning process can run effectively and efficiently.